ESD Biodiversity and Systems Thinking Context in PISA and End-Semester Exams - Suryani, Lilis; Hamdu, Ghullam (Universitas Negeri Semarang, 2025)
PISA becomes a benchmark for the quality of a country’s education. The research was to compare the theme of biodiversity and the system of thinking on the 2018 PISA questions with end-semester exam questions for the 2020/2021 school year in elementary schools. This study used qualitative research with an analysis method for 4-unit PISA questions, 3 sets of end-semester exam questions for grade 5, and 6 questions for elementary school teachers. The results showed that the content related to plants, animals, and microorganisms in the PISA questions was the highest, with a presentation of 95.83%. For the end-semester exam questions, the animal content was the highest percentage of 43.802%. The PISA questions are created thematically, while end-semester exam questions are mostly created per subject. In addition, the content of the structure domain is the highest competency in the system of thinking on PISA questions and end-semester exam questions with presentations of 53.57% and 55.22%, respectively. Students were asked more questions about interconnection analysis. Of course, this content can be learned more by elementary school students. So, that students can have global competence from an early age.